2014
DOI: 10.1155/2014/475919
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I Induces Arginase Activity inLeishmania amazonensisAmastigote-Infected Macrophages through a Cytokine-Independent Mechanism

Abstract: Leishmania (Leishmania) amazonensis exhibits peculiarities in its interactions with hosts. Because amastigotes are the primary form associated with the progression of infection, we studied the effect of insulin-like growth factor (IGF)-I on interactions between L. (L.) amazonensis amastigotes and macrophages. Upon stimulation of infected macrophages with IGF-I, we observed decreased nitric oxide production but increased arginase expression and activity, which lead to increased parasitism. However, stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…The expression of arginase-1 is increased, while NO synthesis is inhibited by catecholamines, making it likely that they promote M2 activation [ 125 , 126 ]. M2 macrophages also produce insulin-like growth factor-1 (IGF-1) [ 106 , 127 , 128 ], which can help tissue regeneration [ 127 ] and have a role in sustaining M2 activation [ 129 ]. Adiponectin gene expression has been shown in mouse adipose tissue macrophages, and its transcript level is diminished when M2 activation is compromised [ 122 ].…”
Section: Overview Of the M2 Macrophage Markersmentioning
confidence: 99%
“…The expression of arginase-1 is increased, while NO synthesis is inhibited by catecholamines, making it likely that they promote M2 activation [ 125 , 126 ]. M2 macrophages also produce insulin-like growth factor-1 (IGF-1) [ 106 , 127 , 128 ], which can help tissue regeneration [ 127 ] and have a role in sustaining M2 activation [ 129 ]. Adiponectin gene expression has been shown in mouse adipose tissue macrophages, and its transcript level is diminished when M2 activation is compromised [ 122 ].…”
Section: Overview Of the M2 Macrophage Markersmentioning
confidence: 99%
“…At 6 hours post-infection, we could detect an 8-fold increase of parasite transcripts in those ears co-injected with PSG, translating to a 4.3-fold increase in parasite burden ( Fig 4A ). From our Affymetrix and RTqPCR results of PSG inoculated into skin we found that PSG significantly increased the early expression of IL-10 and IGF1 (9 and 4-fold change respectively), both known inducers of arginase activity in macrophages [ 59 , 60 ]. This was confirmed in vitro when unstimulated bone-marrow macrophages (BMMΦ) were co-incubated with increasing amounts of PSG, IL-10 or IGF1 for 48 hours ( Fig 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous experimental data, IGF-I can play a role in the progression of Leishmania ( Leishmania ) amazonensis infection by (i) decreasing NO production in macrophages and allowing parasite multiplication, (ii) modulating immune responses by increasing TGF-β and decreasing IFNγ production in promastigote infected macrophages, and (iii) inducing apoptotic mimicry characterized by exposure of phosphatidyl serine on amastigotes but without leading to death [ 15 , 16 ]. However, it is unknown whether similar effects of IGF-I would occur in other Leishmania species.…”
Section: Discussionmentioning
confidence: 99%
“…braziliensis [ 1 ] and different biological effects may occur upon IGF-I stimulus, we initially studied its effect on promastigotes. Focusing on the increase of arginase activity of the parasite, which was seen as main effect of IGF-I [ 16 ], we confronted more complex outcomes that were dependent on Leishmania isolates, whether coming from patients with CL, ML or DL. IGF-I induced higher basal arginase activity in L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation